Macroeconomic effects of fiscal shocks in Portugal - Bova, Elva,Klyviene, Violeta (Publications Office of the European Union, 2019)
This study analyses the impact of fiscal shocks on GDP, inflation and interest rates in Portugal over 1995-2017. In line with the relevant literature, we estimate multipliers using a structural VAR a' la Blanchard and Perotti (2002) based on OECD elasticities. As fiscal shocks, we include changes in direct and indirect taxes on the revenue side, and, on the expenditure side, changes in public consumption, investment and transfers. We find small tax multipliers and larger government consumption multipliers for growth, while short-term responses to shocks in transfer and investment spending are found to be negligible. We find an ambiguous impact of fiscal shocks on inflation, with both indirect and direct taxes having an inflationary impact but government consumption having the contrary impact. Fiscal shocks of an expansionary nature are found to trigger declines in real interest rates, possibly through the inflation channel. The results are robust to different orderings of the variables used in the structural VAR and to the selection of alternative time periods. Overall, the analysis of output multipliers compares well with some other studies conducted on the Portuguese economy and confirms the importance of the disposable income channel in the transmission of fiscal shocks to the rest of the economy.
10.2765/100789
Keywords: Graue Literatur; inflation; fiscal policy; interest; gross domestic product; macroeconomics; Portugal; Fiscal shocks; structural VAR